KUALITAS PRODUK DAN KUALITAS PELANAN SEBAGAI ANTASEDEN KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN (Studi Pada Pelanggan Waroeng Spesial Sambal â€œSSâ€ Cabang Veteran Yogyakarta) - Mulyana, Alo Rahmawati; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2019)
Â The aim of study is toÂ  analyze about effectÂ  productÂ  qualityÂ  andÂ  serviceÂ  qualityÂ  on customerâ€™s satisfaction to build customerâ€™s loyalty at Waroeng Spesial Sambal â€œSSâ€ in the branch of Veteran Yogyakarta. Population in this study are all consumers who makeÂ  purchases at Waroeng Spesial Sambal â€œSSâ€ the branch in theÂ  branch of Veteran Yogyakarta. While the sampleÂ  inÂ  thisÂ  studyÂ  is a portion of consumers who haveÂ  made Â purchases at least twice in the past year. The sampling technique uses purposive sampling. The dataÂ  used in this study is primary data. The numberÂ  of studiesÂ  inÂ  thisÂ  study wereÂ  sixtyÂ  samplesÂ  inÂ  theÂ  city of Yogyakarta whichÂ  were processedÂ  usingÂ  multiple linear regressionÂ  analysisÂ  and mediation analysisÂ  using SPSS 20 for windows. The results of the analysis in this study are: product quality dosenâ€™t have a significant effect on customer satisfaction,Â  service quality has a significant effect on customer satisfaction, customer satisfaction doesnâ€™t have a significant effect on customer loyalty, product qualityÂ  dosenâ€™tÂ  have a significantÂ  effect onÂ  customer loyalty and service quality has a significant effect on customer loyalty of the two independentvariables dosenâ€™t indicate a mediatingÂ  relationshipÂ  with Â customerÂ  satisfaction as a mediator variable.